Contrasting modes of sediment infilling and geomorphic change within a sand dominated dredge pit on the inner Louisiana shelf. (5th November 2022) - Moran, Kelli L.; Xu, Kehui; Wilson, Carol; Lopez, Grant
Abstract: While many sediment transport studies have been performed on mud capped dredge pits (MCDP), there is a paucity of sediment infilling data for sand dominated dredge pits (SDDP) in the Northern Gulf of Mexico (NGoM). In this study, bathymetry, sidescan, and subbottom data were collected in 2018, 2019, and 2020 and sediment cores were collected between the 2019 and 2020 surveys at Block 88: a dredge pit sitting on the sand-dominated Ship Shoal of Louisiana's inner shelf. The crest of Ship Shoal was 5 m below mean sea level before dredging and was excavated to a depth of 10 m below mean sea level after the dredging of 8.4 million m 3 of sediment. Two years after dredging, the northern end of the eastern pit wall accumulated ∼0.09 million tons (approximately 500 m long × 50 m wide × 2.5 m deep) of sediment, driven by westward longshore sediment transport and the deposition of bed load on the shoal crest. Sediment accumulation on the pit bottom was mainly driven by suspended load at a rate of ∼0.1 m yr −1 from 2018 to 2019 and ∼0.2 m yr −1 from 2019 to 2020. Thus, the sediment infilling in Block 88 was from both bed- and suspended-loads from contrasting sources. These pit-bottom sediment accumulation rates are approximately one order of magnitude lower than the predicted rate from a previous empirical modeling study conducted on Ship Shoal and lower than the rates (0.5–2 m yr −1 ) of three other MCDPs on the inner Louisiana shelf. The infilling sediment was patchy and predominantly silt and clay, with lower sidescan reflectivity. The slopes of Block 88's pit walls decreased from ∼20° in 2018 to ∼8° in 2020. These values were smaller than the values of pit wall slopes in MCDPs at a similar stage (i.e., 2–3 years after dredging). Our results indicate that the highest sediment accumulation rates occur immediately adjacent to the eastern pit wall of Block 88, which is down-current of the longshore transport direction. This study helps sand resource managers and policymakers to better plan and design future sediment dredging projects on sandy shoals. This study concludes that the longest axis of a dredge pit should be aligned perpendicular to the longshore transport direction to trap the most sediments for possible reuse. Additionally, both bed load and suspended load should be considered in future modeling to better predict sediment infilling. Highlights: 8.4 million m 3 of sediments were excavated from Block 88 in 2018; it is the second largest dredge pit in Louisiana. ∼102, 500 m 3 of sandy sediment (∼0.15 million tons) have accumulated along the pit wall since the completion of Block 88. Sediment delivery to the pit bottom occurs at a rate of ∼0.2–0.25 m yr −1 and is likely punctuated. The Block 88 dredge pit has migrated minimally since excavation was completed.